The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.18632/oncotarget.10629
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming HSP27-mediated resistance by altered dimerization of HSP27 using small molecules

Abstract: Heat shock protein 27 (HSP27, HSPB1) is an anti-apoptotic protein characterized for its tumorigenic and metastatic properties, and now referenced as a major therapeutic target in many types of cancer. The biochemical properties of HSP27 rely on a structural oligomeric and dynamic organization that is important for its chaperone activity. Down-regulation by small interfering RNA or inhibition with a dominant-negative mutant efficiently counteracts the anti-apoptotic and protective properties of HSP27. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Our previous study showed that SW15 promotes cross-linking of HSP27 to form altered dimers, inhibiting oligomerization of HSP27 [ 13 ]. For sequential further studies for screening of more potent HSP27 cross linkers using synthetic compounds ( Supplementary Figure 1A ) in NCI-H460 cells, we selected 3 chromenone compounds with differing side chain structures, J2, J4 and YK-598-2 because they promoted different amounts of altered cross-linking of HSP27 in both cells and HSP27 protein system (Figure 1A and Supplementary Figure 1B and 1C ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous study showed that SW15 promotes cross-linking of HSP27 to form altered dimers, inhibiting oligomerization of HSP27 [ 13 ]. For sequential further studies for screening of more potent HSP27 cross linkers using synthetic compounds ( Supplementary Figure 1A ) in NCI-H460 cells, we selected 3 chromenone compounds with differing side chain structures, J2, J4 and YK-598-2 because they promoted different amounts of altered cross-linking of HSP27 in both cells and HSP27 protein system (Figure 1A and Supplementary Figure 1B and 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…Small molecule, J2, which promotes altered cross-linking of HSP27, offer a promising approach for inhibition of HSP27, although further research is needed to evaluate the safety and efficacy of this compound in a clinical setting. However, one thing that J2 is more advanced than the previous ones such as SW15 or zerumbone [ 12 , 13 ] is that it can be used for i.p. injection in combined with conventional anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously demonstrated that synthetic compounds zerumbone and SW-15 could induce abnormal cross-linking of the HSP27 protein. Altered crosslinking of HSP27 modifies normal HSP27 dimerization resulting in functional inhibition of HSP27, thereby sensitizing tumors to conventional radiation and chemotherapies 10 , 11 . As an continuous study to further optimize HSP27 inhibitors through abnormal dimerization of HSP27, we have additionally designed and synthesized a small number of chrome-4-one derivatives and found J2 (Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%